The Innovation of Entrepreneurship Education for Intangible Cultural Heritage Inheritance From the Perspective of Entrepreneurial Psychology - Zhou, Jie; Qi, Ji; Shi, Xuefeng (Frontiers in Psychology, 2022)
The purpose is to help college students start their own businesses and protect and develop China's intangible cultural heritage. The entrepreneurship of college students in the field of intangible culture is studied from the perspective of entrepreneurial psychology. First, the related characteristics, main content and research status of college entrepreneurship education are described in detail. Entrepreneurial psychology is divided into entrepreneurial cognition, entrepreneurial emotion and entrepreneurial will. Then, the concept and development status of intangible cultural heritage are briefly summarized to illustrate the importance of inheriting and developing intangible cultural heritage. A questionnaire is designed based on intangible cultural heritage development mode to interview local college students randomly. Finally, the results are analyzed by descriptive statistics. The results show that massive students do not understand the entrepreneurial policy, and only 16% of them know it very well. More than 30% of the students think that entrepreneurship will improve personal responsibility. Nearly 50% of the students believe that entrepreneurship can increase their life experience. Almost 50% of the students have the psychological quality of persistence and courage in entrepreneurship. The final results show that there are great differences in entrepreneurial cognition among students of different grades. Regarding entrepreneurial emotion, there are obvious differences among students of different genders, disciplines and grades. Regarding the entrepreneurial will, there are only differences among students with different grades. In entrepreneurship education, different teaching methods should be adopted for different ages to comprehensively improve the effect of entrepreneurship education for students of all grades and help them obtain good entrepreneurship results. This exploration provides technical support for the inheritance of material and cultural inheritance and contributes to the entrepreneurship education of college students.